Roles of the MST1-JNK signaling pathway in apoptosis of colorectal cancer cells induced by Taurine. Issue 1 (1st January 2018) - Liu, Zhuoqi; Xia, Yanqin; Zhang, Xiali; Liu, Liqiao; Tu, Shuo; Zhu, Weifeng; Yu, Lehan; Wan, Huifang; Yu, Bo; Wan, Fusheng
ABSTRACT: The aim of this study was to observe the impact of the mammalian sterile 20-like kinase 1-c-Jun N-terminal kinase (MST1-JNK) signaling pathway on apoptosis in colorectal cancer (CRC) cells induced by Taurine (Tau). Caco-2 and SW620 cells transfected with p-enhanced green fluorescent protein (EGFP)-MST1 or short interfering RNA (siRNA)-MST1 were treated with Tau for 48 h. Apoptosis was detected by flow cytometry, and the levels of MST1 and JNK were detected by western blotting. Compared with the control group, 80 mM Tau could significantly induce apoptosis of CRC cells, and the apoptotic rate increased with increasing Tau concentration ( P  < 0.01). Meanwhile, the protein levels of MST1 and phosphorylated (p)-JNK in Caco-2 cells increased significantly ( P  < 0.01). The apoptotic rate of the p-EGFP-MST1 plasmid-transfected cancer cells was significantly higher than that of the control group ( P  < 0.05); however, the apoptotic rate of the p-EGFP-MST1+Tau group was increased further ( P  < 0.01). Silencing the MST1 gene could decrease the apoptotic rate of cancer cells, and Tau treatment could reverse this decrease. Blocking the JNK signaling pathway significantly reduced the Tau-induced apoptotic rate of CRC cells. Thus, the MST1-JNK pathway plays an important role in Tau-induced apoptosis of CRC cells.